(untitled) (Research, Society and Development, 2025)
Cesarean section rates are increasingly rising to the detriment of the progressive reduction in the number of natural births, a fact intrinsically linked to socioeconomic and cultural issues. Currently, the Brazilian prevalence of cesarean deliveries reaches 84.76% in supplementary healthcare. Thus, this study aims to analyze the absolute frequency of cesarean and normal deliveries, as well as to compare their prevalence, during the period from 2021 to 2024, in the state of Minas Gerais, Brazil. This is a documentary study that uses secondary data, with descriptive, exploratory, cross-sectional, and retrospective characteristics, and adopts a quantitative approach. Data were extracted from the database of the Department of Health Information and Informatics of the Brazilian Unified Health System (DATASUS). The focus was on women who had cesarean and normal deliveries between January 2021 and June 2024 in Minas Gerais, Brazil. Within the analyzed scope, more than 26 million births were reported over these four years, of which 50.5% were cesarean deliveries, performed in both public and private healthcare services. Thus, it is possible to confirm the almost pathological prevalence of surgical births over natural ones, contrary to the official recommendation of the World Health Organization (WHO) of 10 to 15%.